Relative Incidence of Insect-Pest Complex in Bt and non-Bt Cotton Cultivars - Raja, B.; Singh, T. V. K.; Lakshmi, K. Vijaya; Sreenivas, C. H. (International Journal of Bio-resource and Stress Management, 2023)
An investigation was carried out to find out the relative incidence of pest complex in three cottoncultivars viz., in MECH 162 Bt, MECH 162 non-Bt. The treatments were replicated nine times in randomized block design. The incidence of leafhopper, aphid and whitefly was found in all the three cultivars throughout the crop season, but the worm, Helicoverpa armigera and spotted bollworm, Earias vittella infestation was comparatively less in MECH 162 Btcotton than other cultivars. The maximum incidence of H. armigera was recorded during 14th and 15th week after sowing in all three cultivars.